Analysis of Cattle and Coconut Integration Business (Cocos nucifera) in Dampelas District, Donggala Regency - Susiana, Neni; Syukur, Suharno H. (AgriSains, 2021)
Livestock-coconut integration pattern is characterized by a close relationship between the plant and livestock components in a farming activity or in an area. This study aims to determine the income of farmers and the feasibility of integrating cattle with coconut plantations in Dampelas sub-district, Donggala district. This research was conducted in Dampelas District, Donggala Regency. The research site was chosen purposely (Purposive) with the consideration that in this area many farmers are implementing the business pattern of integrating cattle with coconut (Cocos nucifera) This research was conducted from October to December 2019. Based on the analysis of the cow-coconut integration effort (Cocos Nucifera) in Balaesang District, Donggala Regency. coconut sales were Rp.24.178.826 / year and total sales of cattle were Rp.61.837.745 / year, so the total income was Rp.86.016.571 / year. The R / C for the coconut plantation business is 8.67 and the R/C for the cattle business is 105.56 feasible to be developed.